Nodular lesions of the skin. - Bonifazi, E. (European Journal of Pediatric Dermatology, 1999)
A cutaneous nodule is a circumscribed relief of the skin, which persists for weeks. In this chapter are included the skin disorders characterized by nodular infiltration of the dermis, both of the inflammatory (granuloma) and proliferative type. We will initially treat the inflammatory or granulomatous nodular lesions, which are caused by infectious agents -viruses, bacteria and fungi-, by infestation -leishmaniasis, scabies and tick bite, by other agents -post-traumatic granuloma and granuloma gluteale infantum- or by not defined causes -annular granuloma, granuloma faciale and sarcoidosis-.